Complete mitochondrial genome of Hemiptelea davidii (Ulmaceae) and phylogenetic analysis - Liu, Hua-Bo (Mitochondrial DNA B Resour, 2019)
Hemiptelea davidii (Hance) Planch is a potential valuable forest tree in arid sandy environments. Here, the complete mitochondrial genome of H. davidii was assembled using a combination of the PacBio Sequel data and the Illumina Hiseq data. The mitochondrial genome is 460,941 bp in length, including 37 protein-coding genes, 19 tRNA genes, and three rRNA genes. The GC content of the whole mitochondrial genome is 44.84%. Phylogenetic analyses indicated that H. davidii is close with Cannabis and Morus species.